Tamaki Mihic. 2020. Re-imagining Japan after Fukushima. Canberra: Australian National University Press. Ebook ISBN 9781760463540. https://doi.org/10.22459/RJF.2020 - Tapia Silva, Nancy Alejandra (Estudios de Asia y África, 2022)
Tamaki Mihic. 2020. Re-imagining Japan after Fukushima. Canberra: Australian National University Press. Ebook ISBN 9781760463540. https://doi.org/10.22459/RJF.2020